Return to sport after conservative treatment of elbow dislocation in judoka - Lambert, C.; Ritzmann, R.; Geßlein, M.; Bouillon, B.; Höher, J.; Akoto, R.; Wafaisade, A. (Sportverletzung Sportschaden, 2023)
Background: Injuries to the elbow are frequent in judo combat, but studies on down-time and effect on performance after conservative treatments are rare. This issue is particularly relevant for elbow dislocations in high-performance patients such as elite athletes. The purpose of this study was to evaluate (1) time-loss and (2) the regained level of performance in judoka after conservative treatment of simple elbow dislocation.